Safety and immunogenicity of the BNT162b2 mRNA Covid-19 vaccine in patients with chronic lymphocytic leukemia: a prospective study. (May 2022) - Diamantopoulos, Panagiotis T.; Stafylidis, Christos; Vlachopoulou, Dimitra; Kontandreopoulou, Christina-Nefeli; Giannakopoulou, Nefeli; Vardaka, Maria; Mpouhla, Anthi; Mastrogianni, Elpida; Variami, Eleni; Galanopoulos, Athanasios; Pappa, Vasiliki; Psichogiou, Mina; et al.
Introduction: Immunization of patients with chronic lymphocytic leukemia (CLL) with vaccines against several infectious diseases has proven insufficient. Data on seroconversion of patients with CLL after vaccination against severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) are still young, but accumulating evidence shows low seroconversion rates. Methods: We conducted a prospective, noninterventional study evaluating the safety and immunogenicity of two doses of the BNT162b2 mRNA Covid-19 vaccine, administered 21 days apart in consecutive adult patients with CLL. Patients vaccinated with other vaccines against SARS-CoV-2, with a history of confirmed Coronavirus Disease 19 (COVID-19), with known human immunodeficiency virus infection, or with an inability to provide written informed consent were excluded. Sera were tested before the first and after the second dose of the vaccine for anti-SARS-CoV-2 receptor binding domain (RBD) spike protein IgG (anti-RBD), using the Abbott SARS-CoV-2 IgG II Quant assay (Abbott Laboratories, Abbott Park, IL, USA), with a cutoff value for seroconversion at 50 AU/ml. Results: Sixty-one patients (28 males/33 females) with CLL, with a median age of 61 years, were included in the study. The majority of the patients (82.0%) were lower (0–2) stage per the RAI staging system. The seroconversion rate at 14 days after the second dose was 45% and was correlated with RAI stage (0–2 versus 3–4; 51.0% versus 18.3%, p  = 0.047), the treatment status (treatment naïve, previously treated, or actively treated patients; 63.0% versus 40.0% versus 26.1%, respectively, p  = 0.031), the number of previous treatment lines (0–2 versus >2; 55.3% versus 8.3%, p  = 0.004), and the platelet count of the patients (over or under 100 × 10 9 /L; 52.9% versus 10.0%, p  = 0.015). Moreover, there was a positive linear relationship between the antibody titers and the gamma-globulin levels ( r  = 0.182, p  = 0.046) and platelet count ( r  = 0.277, p  = 0.002). Finally, patients actively treated with venetoclax had higher antibody titers than those treated with ibrutinib (15.8 AU/ml versus 0.0 AU/ml, p  = 0.047). No safety issues were identified while the emergence of adverse events was not correlated with immunogenicity. Discussion: This study confirms results from previous studies on the low seroconversion rates in patients with CLL vaccinated with the BNT162b2 mRNA Covid-19 vaccine and on the detrimental effect of advanced disease and multiple treatment lines on seroconversion, while it is suggested that treatment with venetoclax may offer a chance for higher antibody titers, suggesting a treatment strategy change during the pandemic provided that this result is confirmed by larger studies specifically designed to address this issue.